Influences on fertility control and early parenthood in a rural district of Zimbabwe - Chemhuru, Nyengeterai; Matunhu, Jephias; Shumba, Almon; Nyamande, Winifrida S.; Mahlatini, Janet P. (National Inquiry Services Centre, 2016)
This study investigated influences on fertility control and early parenthood among teenage learners from a rural district in Zimbabwe. Data on perceived influences on risks for early parenthood were collected from 1320 female secondary school learners (mean age=16 years, SD=1.35) using a semi-structured questionnaire. The data were analyzed descriptively. Teenagers believed to be at risk for early parenthood from early sexual debut, material poverty and peer influences to engage in sexual relationships.